What is your MBA for? What's the story?. Issue 1 (February 2017) - Ruth, Damian
This article shows how the MBA plays a role in some students' lives that goes beyond conscious cost–benefit analyses and instrumental value and engages the personal and intimate. It presents a thematic analysis of essays written by MBA students exploring what their MBA was for. The analysis revealed that the MBA functioned as an element or character in a life story and how, in some instances, doing the MBA was not about the MBA as such. The article advances our understanding of the MBA as an element in a life story, as a rite of passage, and as part of the intersection of boundaryless careers and changeable life patterns. Enhancing the awareness of this on the part of students may improve their understanding of what they are doing by embarking on an MBA and could enhance the ability of faculty and business schools to address the sometimes less explicit interests of their students. The article also confirms the value of a qualitative 'storied' approach to the study of the MBA.